Impact of sodium chloride on breakfast cereal products - Moreau, Lydie (2009)
To reduce the amount of sodium chloride in breakfast cereals without changing their properties, it is necessary to understand the role of this salt. Hence, a model system was developed. This model, composed of native waxy maize starch, glucose and a mixture of amino-acids generated similar colour and residual volatiles after heating compared to commercial breakfast cereals. Systematically designed experiments used this model to study the influence of NaCl concentration (0 % to 5.44 %) on colour, residual volatiles and acrylamide formation. It was found that higher NaCl concentration led to darker products (p<0.05) and significantly decreased acrylamide formation in the model systems. However, it did not have a significant impact on residual volatile levels. These findings were confirmed by observations made on wheat, wheat and rice mixture, com and rice commercial cereals.